PRImary care Management of lower Urinary tract Symptoms in men: protocol for development and validation of a diagnostic and clinical decision support tool (the PriMUS study). Issue 6 (30th June 2020) - Pell, Bethan; Thomas-Jones, Emma; Bray, Alison; Agarwal, Ridhi; Ahmed, Haroon; Allen, A Joy; Clarke, Samantha; Deeks, Jonathan J; Drake, Marcus; Drinnan, Michael; Dyer, Calie; Hood, Kerenza; et al.
Abstract : Introduction: Lower urinary tract symptoms (LUTS) is a bothersome condition affecting older men which can lead to poor quality of life. General practitioners (GPs) currently have no easily available assessment tools to help effectively diagnose causes of LUTS and aid discussion of treatment with patients. Men are frequently referred to urology specialists who often recommend treatments that could have been initiated in primary care. GP access to simple, accurate tests and clinician decision tools are needed to facilitate accurate and effective patient management of LUTS in primary care. Methods and analysis: PRImary care Management of lower Urinary tract Symptoms (PriMUS) is a prospective diagnostic accuracy study based in primary care. The study will determine which of a number of index tests used in combination best predict three urodynamic observations in men who present to their GP with LUTS. These are detrusor overactivity, bladder outlet obstruction and/or detrusor underactivity. Two cohorts of participants, one for development of the prototype diagnostic tool and other for validation, will undergo a series of simple index tests and the invasive reference standard (invasive urodynamics). We will develop and validate three diagnostic prediction models based on each condition and then combine them with management recommendations to form a clinical decision support tool. Ethics and dissemination: Ethics approval is from the Wales Research Ethics Committee 6. Findings will be disseminated through peer-reviewed journals and conferences, and results will be of interest to professional and patient stakeholders. Trial registration number: ISRCTN10327305 .